Core-shell catalyst as well as preparation method and application thereof

By combining α-MnO2 nanowires with graphite phase carbon nitride to form a catalyst for core-shell structure, the problem of difficulty in efficiently handling waste refrigerants in the prior art is solved, and the efficient degradation effect under the photothermal synergistic system is achieved.

CN119702039APending Publication Date: 2025-03-28DALIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821572.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and at low cost to deal with waste refrigerants, especially refrigerants with high impurities and high concentrations, resulting in environmental pollution and global climate warming problems.

Method used

The catalyst is prepared by combining the α-MnO2 nanowires with graphite phase carbon nitride to form a core-shell structure, and the catalyst is prepared by sol-gel method and hydrothermal reaction method to achieve efficient degradation of the refrigerant.

Benefits of technology

This catalyst can significantly improve the activity of manganese-based oxidation catalyst under the photothermal synergistic system, achieve efficient degradation of refrigerant, have high degradation efficiency, strong thermal stability, and can achieve mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702039A_ABST
    Figure CN119702039A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell catalyst and a preparation method and application thereof, the catalyst is an interface packaging structure composed of an alpha-MnO2 nanowire of an inner core and an outer shell coating the surface of the inner core, and the outer shell is graphite phase carbon nitride. According to the preparation method, a g-C3N4 blocky body phase material forms stable carbon nitride in a sol-gel state by adopting a neutral hydrothermal reaction, and synthesis of a core-shell material and construction of an interface built-in electric field are realized by combining a novel method of in-situ deposition and low-temperature polymerization; cN micromolecules are successfully polymerized to the surface of the alpha-MnO2 nanowire under a low-temperature condition through a solid nuclear magnetism technology and an infrared spectrum technology, the alpha-MnO2 (at) g-C3N4 ultrathin nanowire core-shell photocatalyst with large conjugate graphite-like C3N4 as a shell layer and the alpha-MnO2 nanowire as a core layer is formed, the catalytic effect is good, the degradation efficiency is high, the thermal stability is high, and mass production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic technology, and more specifically, to a core-shell catalyst and a preparation method and application thereof. Background Art

[0002] Synthetic refrigerants are essential products in modern industrial production and daily life, but the environmental problems they bring are gradually gaining widespread attention. Hydrofluorocarbon (HFCs) refrigerants do not damage the ozone layer, so they are widely used as substitutes for CFCs and HCFCs. However, the global warming potential (GWP) of some HFCs is still very high, which will also have a great impact on global warming.

[0003] During the entire waste refrigerant disposal process, a large amount of waste refrigerant gas evaporates into the atmosphere, causing environmental pollution. For refrigerants with more impurities and higher concentrations, direct disposal will produce high-concentration acidic hydrogen fluoride or hydrogen chloride gas, which poses certain technical and equipment problems. At present, no efficient and low-cost method for treating waste refrigerants has been developed, and the degradation products and related degradation mechanisms are still unclear, requiring further in-depth research.

[0004] This patent adopts photothermal synergistic catalytic oxidation as an emerging method for air pollution control. When semiconductor materials are irradiated, the energy generated by electron-hole pairs is similar to the band gap, and the excited electrons eventually return to low energy levels and relax and release energy through radiated photons.

[0005] However, in the core-shell structure, the shell thickness of the photocatalytic semiconductor needs to be limited. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and to provide a core-shell catalyst and a preparation method and application thereof. The catalyst with a core-shell structure prepared by mixing carbon nitride and α-MnO2 in a sol-gel state and then polymerizing them at low temperature can overcome the limitations of a single photocatalytic process or a thermal catalytic process and improve the activity of the manganese-based oxidation catalyst.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A core-shell catalyst, the catalyst is an interface packaging structure composed of an inner core of α-MnO2 nanowires and an outer shell coated on the surface of the inner core, the outer shell is graphite phase carbon nitride; the mass ratio of the α-MnO2 nanowires to the graphite phase carbon nitride is (1-30):1, preferably 10:1.

[0009] Optionally, the diameter of the α-MnO2 nanowire is 20 nm.

[0010] Optionally, the thickness of the shell is 1 nm.

[0011] The present invention also discloses a method for preparing the core-shell catalyst as described above, comprising the following steps:

[0012] (1) heating dicyandiamide to 550°C at a heating rate of 2.3°C / min to 3°C / min under the protection of an inert gas and keeping the temperature for 4 hours to obtain bulk-g-C3N4;

[0013] (2) dissolving the bulk-g-C3N4 in water and performing a hydrothermal reaction to obtain a CN transparent solution;

[0014] (3) After adding MnSO4·H2O to water, KMnO4 solution is added dropwise to form a suspension, the suspension is reacted at 150°C for 12 hours, cooled to room temperature, washed, and freeze-dried to dehydrate, thereby obtaining α-MnO2 nanowires;

[0015] (4) adding the α-MnO2 nanowires to the CN transparent solution, mixing, freeze-drying, and calcining at 300°C for 4 hours to obtain the core-shell catalyst.

[0016] Optionally, in step (2), the mass volume ratio of bulk-g-C3N4 and water is 1:40.

[0017] Optionally, in step (2), the temperature of the hydrothermal reaction is 210° C., and the time of the hydrothermal reaction is 8 h to 10 h.

[0018] Optionally, in step (3), the mass volume ratio of the MnSO4·H2O and the KMnO4 solution is 2:1.

[0019] Optionally, in step (3), the concentration of the KMnO4 solution is 2.857 mol / L.

[0020] Optionally, in step (4), the molar ratio of the CN transparent solution to the α-MnO2 nanowires is 1:10.

[0021] The present invention also discloses an application of the core-shell catalyst as described above, or the core-shell catalyst prepared by the preparation method as described above, in degrading refrigerants.

[0022] Optionally, weigh the core-shell catalyst mentioned above and put it into a reactor. After locking the reactor, use R134a, standard gas and oxygen for gas distribution, place the reactor on a heating plate at 120°C, cover its light window with a shading sheet, turn on the xenon lamp, adjust the current to 15A, preheat for 20min to 30min, remove the shading sheet, and place the xenon lamp close to the reactor so that the incident light directly hits the catalyst for photothermal reaction for 30min to 180min, so as to achieve the degradation of the refrigerant.

[0023] Optionally, take the catalyst and spread it on the bottom of the reactor cavity for each reaction to ensure that the bottom is completely covered by the catalyst. Then evacuate the reactor and inject each component gas in turn, including 6mL of R134a and 14mL of standard gas. The content of oxygen and nitrogen is proportioned according to the conditions required by the experiment, and finally ensure that the reactor is in a slightly positive pressure state at room temperature.

[0024] Optionally, the gas composition ratio is 6mL R134a, 14mL standard gas and 36mL oxygen, the reaction light source is an experimental xenon lamp, and filtered with a 420nm filter, the reaction starts at 0min, and then 500μL is extracted from the reactor every 20min and injected into the gas chromatograph to detect the gas composition.

[0025] Implementing the embodiments of the present invention will have the following beneficial effects:

[0026] (1) The present invention uses a neutral hydrothermal reaction to convert the g-C3N4 bulk phase material into a stable sol-gel carbon nitride, and combines it with a new method of in-situ deposition and low-temperature polymerization to achieve the synthesis of α-MnO2@g-C3N4 ultra-thin nanowire core-shell materials and the construction of an interfacial built-in electric field; and uses solid-state nuclear magnetic resonance technology and infrared spectroscopy technology to characterize that CN small molecules have been successfully polymerized onto the surface of α-MnO2 nanowires under low temperature conditions to form an α-MnO2@g-C3N4 ultra-thin nanowire core-shell photocatalyst with a large conjugated graphite phase C3N4 as the shell layer and an α-MnO2 nanowire as the core layer.

[0027] (2) The preparation method provided by the present invention first utilizes the sol-gel method to make the basic carbon nitride form a transparent solution, and then adds α-MnO2 for encapsulation and coating to obtain a catalytic material; the synthesis steps are simple, and the prepared composite material has good catalytic effect, high degradation efficiency, strong thermal stability, and can be mass-produced.

[0028] (3) The catalytic material prepared by the present invention has a large number of reactive active sites on its surface, which is beneficial to increasing the absorption rate of the composite material to visible light and the migration rate of photogenerated carriers on the surface of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1XRD spectra of α-MnO2@g-C3N4 with five mass ratios (1%, 5%, 10%, 15%, and 30%) in Example 1 of the present invention.

[0030] Figure 2 FT-IR spectra of pure g-C3N4, α-MnO2 nanowires and a series of core-shell structure samples of Example 1 of the present invention.

[0031] Figure 3 These are scanning electron microscope images of Example 1 of the present invention, wherein (a) to (b) are electron microscope images of α-MnO2 nanowires; and (c) to (d) are electron microscope images of 10% α-MnO2@g-C3N4.

[0032] Figure 4 This is a comparison chart of the degradation efficiency of α-MnO2@g-C3N4 to R134a at five mass ratios (1%, 5%, 10%, 15%, and 30%) of Example 1 of the present invention.

[0033] Figure 5 This is a comparison chart of the degradation efficiency of R134a by 110% α-MnO2@g-C3N4 under different photothermal conditions in the embodiment of the present invention.

[0034] Figure 6 This is a graph showing the degradation efficiency of R134a by 110% α-MnO2@g-C3N4 under different light intensities in an embodiment of the present invention. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0036] Example 1

[0037] The preparation method of the core-shell catalyst of this embodiment comprises the following steps:

[0038] (1) Preparation of small molecule sol-gel carbon nitride by sol-gel method: 10 g of dicyandiamide was weighed into a crucible, placed in the constant temperature zone of a muffle furnace, and heated from 30 °C to 550 °C at a heating rate of 2.3 °C / min and maintained for 4 h to obtain bulk-g-C3N4 with a yield of 40%.

[0039] (2) Weigh 0.5 g of g-C3N4 powder into a 50 mL hydrothermal reactor, add 35 mL of deionized water, tighten the kettle, and place it in an oven at 210 °C for 8 h to obtain sol-gel carbon nitride.

[0040] (2) Preparation of α-MnO2 nanowires by hydrothermal method: First, 1.166 g of MnSO4·H2O was added to 80 mL of deionized water under continuous stirring. Subsequently, 20 mL of KMnO4 (0.727 g) solution was added dropwise to the dispersion to form a suspension under constant stirring for 20 min. Then, the suspension was transferred to a 120 mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 150 °C for 12 h. After cooling to room temperature, the product was washed with deionized water to remove impurities. Finally, the obtained sample was directly dehydrated by a freeze-drying process.

[0041] (3) Add a certain amount of α-MnO2 powder to the sol-gel carbon nitride, stir thoroughly to mix evenly, and freeze-dry to obtain an α-MnO2 / g-C3N4 core-shell structure sample. Take the α-MnO2@g-C3N4 sample and treat it in a tube furnace at 300°C under N2 protection for 4 hours to obtain the product. According to different proportions, they are named α-MnO2@g-C3N4-1%, α-MnO2@g-C3N4-5%, α-MnO2@g-C3N4-10%, α-MnO2@g-C3N4-15%, and α-MnO2@g-C3N4-30%.

[0042] Example 2

[0043] This example uses the catalyst prepared in Example 1 to analyze its application effect in the degradation of R134a, as follows: Weigh 10 mg of α-MnO2@g-C3N4 prepared in Example 1 and put it into the reaction device. After loading the catalyst and locking the reactor, the air tightness of the reactor is verified by evacuating to vacuum and keeping it for 20 minutes. Using a ratio of 6 mL of R134a, 14 mL of standard gas and 36 mL of oxygen, after the gas distribution is completed, the reactor is placed on a heating plate at 120 ° C, and its light window is covered to eliminate the influence of light during the heating process. Turn on the xenon lamp, adjust the current to 15A, and preheat for at least 20 minutes to stabilize its light intensity. After the gas temperature in the reactor is stabilized near the set value and the xenon lamp is preheated, remove the reactor shade, and place the xenon lamp close to the reactor so that the incident light directly hits the catalyst, and place the xenon lamp close to the reactor so that the incident light directly hits the catalyst. This moment is the reaction 0min moment. After that, 500 μL of gas was extracted from the reactor every 20 min and injected into the gas chromatograph to detect the gas composition.

[0044]

[0045] Example 3

[0046] This example uses the catalyst α-MnO2@g-C3N4-10% prepared in Example 1 to analyze its application effect in the degradation of R134a.

[0047] Compared with Example 2, this embodiment is different in that the reaction conditions are controlled differently, and three conditions are set respectively: room temperature without light, 120°C without light, and 120°C + 15A light. The rest are the same and will not be repeated here.

[0048] Example 4

[0049] This example uses the catalyst α-MnO2@g-C3N4-10% prepared in Example 1 to analyze its application effect in the degradation of R134a.

[0050] The present embodiment is different from the embodiment 2 in that the reaction conditions are controlled differently, the temperature of the heating plate is controlled to 80° C., the current of the xenon lamp is adjusted to 12.5A, 15A, and 17.5A in sequence, and the rest are the same and will not be described again.

[0051] Figure 1 This is the XRD test result of α-MnO2@g-C3N4 with five mass ratios (1%, 5%, 10%, 15% and 30%) prepared in Example 1 of the present invention. The characteristic diffraction peaks at 12.7°, 18.1°, 28.8°, 37.5°, 49.8° and 60.2° correspond to (110), (200), (310), (211), (411) and (521) crystal planes respectively, which are consistent with the peak intensities and peak positions corresponding to the standard card (JCPDS, #44-0141). The characteristic diffraction peaks of pure g-C3N4 are 13.0° and 27.4°, which are attributed to the (100) and (002) crystal planes respectively. When the g-C3N4 content exceeds 10wt%, the addition of g-C3N4 gradually affects the crystal structure of MnO2, and the characteristic diffraction peaks generated at 12.7° and 18.0° begin to shift to low angles. At this time, the lattice spacing of g-C3N4 decreases, and other crystal structures of MnO2 begin to appear, proving that the CN precursor has a strong interaction with α-MnO2 during the low-temperature polymerization process on the α-MnO2 surface, inducing α-MnO2 to transform into γ-MnO2, and the characteristic peaks of g-C3N4 begin to appear.

[0052] Figure 2 The FT-IR spectra of the pure g-C3N4, α-MnO2 nanowires and a series of core-shell structure samples prepared in Example 1 of the present invention are shown in FIG. Figure 2 It can be seen that the typical stretching vibration peak of CN hybridization in the g-C3N4 molecular skeleton is between 1200 and 1700 cm -1 The peak intensity in this region indicates the degree of conjugation of the g-C3N4 skeleton. From the core-shell structure samples, it can be seen that the obvious g-C3N4 characteristic infrared peak is between 1250-1750cm -1In the range of 542 cm-1, a large red shift can be seen compared with pure g-C3N4, indicating that a new valence bond is formed at the interface between g-C3N4 and α-MnO2. -1 and 741cm -1 The peak of Mn-O bond bending vibration appears, and the vibration frequency changes and shifts to a lower angle after the introduction of g-C3N4. This is because g-C3N4 produces a conjugated effect with α-MnO2, which optimizes the electron distribution, constructs an interface built-in electric field, and makes the electronic structure more stable.

[0053] Figure 3 The present invention conducted a scanning electron microscope test on the α-MnO2 nanowires and 10% α-MnO2@g-C3N4 prepared in Example 1. Figure 3 It can be seen from (a) to (b) that the hydrothermal α-MnO2 presents a fibrous morphology with uniform thickness, uniform fiber distribution, good dispersion, and no obvious clustering phenomenon. Figure 3 (c) to (d) show that the diameter of the α-MnO2 nanowire becomes larger after being encapsulated by g-C3N4, and the wire body becomes fuller and more uniform, proving that the g-C3N4 layer is successfully polymerized on the α-MnO2 nanowire.

[0054] Figure 4 The relative concentration-time curves of R134a degradation under visible light by five different mass ratios of α-MnO2@g-C3N4 prepared in Example 1 of the present invention. Figure 4 It shows that the degradation performance of α-MnO2@g-C3N4 composite materials obtained by different g-C3N4 dosages is different. Among them, 10% α-MnO2@g-C3N4 has the strongest degradation effect on R134a within 120 minutes, which can reach about 97%, effectively improving the photothermal catalytic degradation effect of initial g-C3N4 and α-MnO2. 10% α-MnO2@g-C3N4 loading reaches the best, and amorphous carbon nitride is evenly and densely distributed on α-MnO2 nanowires, which makes α-MnO2@g-C3N4 nanowires have strong light response ability and promotes the generation and migration of photogenerated electrons.

[0055] Figure 5 The relative concentration-time curve of 10% α-MnO2@g-C3N4 prepared by the present invention for degradation of R134a under different photothermal conditions. Figure 5 It can be seen that the degradation rate of R134a under 120℃+15A illumination conditions is significantly faster than the degradation rate under 120℃ without illumination and 15A illumination at room temperature. It proves that the catalytic reaction rate of photothermal synergy is much higher than that of simple thermal catalysis and photocatalysis, and can achieve R134a degradation under mild conditions.

[0056] Figure 6The relative concentration-time curve of 10% α-MnO2@g-C3N4 prepared by the present invention degrading R134a at different light intensities. Figure 6 It can be seen that as the light intensity increases, the degradation efficiency increases significantly, but as the light intensity increases, the degradation efficiency increases more slowly. When the light intensity increases, the efficiency of generating free radicals on the catalyst surface increases, which accelerates the degradation rate of R134a.

[0057] In summary, the present invention successfully synthesized a carbon nitride encapsulated α-MnO2 nanowire composite material, broadened the photoresponse range of the catalyst through appropriate energy band matching, suppressed the recombination of photogenerated carriers, and improved the catalytic oxidation performance of the catalyst under a photothermal synergistic system.

[0058] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A core-shell catalyst, characterized in that: The catalyst is an interface encapsulation structure composed of an inner core of α-MnO2 nanowires and an outer shell coated on the surface of the inner core, wherein the outer shell is graphite phase carbon nitride; The mass ratio of the α-MnO2 nanowires to the graphite phase carbon nitride is (1-30):

1.

2. The core-shell catalyst according to claim 1, characterized in that The diameter of the α-MnO2 nanowire is 20nm; The thickness of the shell is 1 nm.

3. A method for preparing a core-shell catalyst as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: (1) heating dicyandiamide to 550°C at a heating rate of 2.3°C / min to 3°C / min under the protection of an inert gas and keeping the temperature for 4 hours to obtain bulk-g-C3N4; (2) dissolving the bulk-g-C3N4 in water and performing a hydrothermal reaction to obtain a CN transparent solution; (3) After adding MnSO4·H2O to water, KMnO4 solution is added dropwise to form a suspension, the suspension is reacted at 150°C for 12 hours, cooled to room temperature, washed, and freeze-dried to dehydrate, thereby obtaining α-MnO2 nanowires; (4) adding the α-MnO2 nanowires to the CN transparent solution, mixing, freeze-drying, and calcining at 300°C for 4 hours to obtain the core-shell catalyst.

4. The preparation method according to claim 3, characterized in that: In step (2), the mass volume ratio of bul kg-C3N4 to water is 1:40; The temperature of the hydrothermal reaction is 210° C., and the time of the hydrothermal reaction is 8 h to 10 h.

5. The preparation method according to claim 3, characterized in that: In step (3), the mass volume ratio of the MnSO4·H2O to the KMnO4 solution is 2:1; The concentration of the KMnO4 solution is 2.857 mol / L.

6. The preparation method according to claim 3, characterized in that: In step (4), the molar ratio of the CN transparent solution to the α-MnO2 nanowires is 1:

10.

7. Use of the core-shell catalyst as claimed in any one of claims 1 to 3, or the core-shell catalyst prepared by the preparation method as claimed in any one of claims 4 to 6 in degrading refrigerants.

8. The use according to claim 7, characterized in that: The core-shell catalyst is weighed and placed in a reactor. After locking the reactor, R134a, standard gas and oxygen are used for gas distribution. The reactor is placed on a heating plate at 120°C, and its light window is covered with a shading sheet. The xenon lamp is turned on, and the current is adjusted to 15A. After preheating for 20 to 30 minutes, the shading sheet is removed, and the xenon lamp is placed close to the reactor so that the incident light directly irradiates the catalyst for a photothermal reaction for 30 to 180 minutes to achieve the degradation of the refrigerant.

9. The use according to claim 8, characterized in that: The light source used for the photothermal reaction is an experimental xenon lamp, which is filtered with a 420nm filter.